A composite curing agent, titanium gypsum solidified soil and preparation method and application thereof
By using calcium salt and silicate compound as early strength agents, polyvinylamide and polyethylene glycol compound as thickeners, and combined with ore powder, lime, cement and dispersants, the problems of high soluble salt content and low mechanical strength in titanium gypsum roadbed materials are solved, and efficient resource utilization and environmentally friendly effects of titanium gypsum cured soil are achieved.
Patent Information
- Application Number
- CN202411619163.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to effectively reduce the soluble salt content in titanium gypsum roadbed materials and improve the strength of titanium gypsum roadbeds, making it difficult to achieve large-scale utilization of titanium gypsum.
The combination of calcium salt and silicate is used as early strength agents, and the combination of polyvinylamide and polyethylene glycol is used as thickening agents. Combined with ore powder, lime, cement and dispersant, each component works together to improve the defects of high liquid limit, difficulty in grading and low mechanical strength of titanium gypsum.
It significantly reduces the soluble salt content in the solidified soil of titanium gypsum, improves its mechanical properties and California load-bearing ratio (CBR), helps to achieve large-scale resource utilization of titanium gypsum, and reduces environmental pollution.
Smart Images

Figure BDA0005133010730000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium gypsum resource utilization, and particularly relates to a composite curing agent, titanium gypsum solidified soil, and a preparation method and application thereof. Background Art
[0002] With the rapid development of infrastructure construction, the demand for roadbed materials is growing. Traditional roadbed fillers such as sand and stone chips are limited in resources and have environmental pollution problems. Therefore, seeking a sustainable and environmentally friendly roadbed filler has become a hot topic in current research. Titanium gypsum, as an industrial by-product, has broad resource prospects and environmental advantages. Its application in the preparation of roadbed fillers has good market prospects and development potential.
[0003] Titanium gypsum is a type of gypsum solid waste. It is produced by adding lime or carbide slag to the acidic wastewater of the sulfuric acid process for preparing titanium dioxide. Its main component is dihydrate gypsum. Due to the high viscosity, high water content and complex impurities of titanium gypsum, its comprehensive utilization rate is low, only about 10%. At present, most gypsum is not effectively utilized, and most of it is piled up in the open air, occupying a large amount of land resources. Long-term exposure to wind and sun will form dust and cause air pollution. In the rainy season, harmful impurities will be carried by rainwater, which will pollute crops and seep into groundwater sources, polluting the soil, and posing a threat to human health.
[0004] At present, there is an existing technology for applying titanium gypsum to roadbed materials. However, due to the characteristics of titanium gypsum such as high soluble salt content, high natural water content, poor particle grading, high liquid limit, and low mechanical strength, the obtained roadbed materials have high soluble salt content and low mechanical strength, which cannot meet actual needs and it is difficult to achieve large-scale utilization of titanium gypsum.
[0005] Therefore, it is of great significance to provide a composite curing agent that can significantly reduce the soluble salt content in titanium gypsum roadbed materials and improve the strength of titanium gypsum roadbed. Summary of the invention
[0006] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial option. Specifically, the present invention provides a composite curing agent, which is used to treat titanium gypsum, thereby reducing the content of soluble salts in the prepared titanium gypsum-cured soil, reducing environmental pollution, improving the mechanical properties of the titanium gypsum-cured soil, and realizing large-scale resource utilization of titanium gypsum.
[0007] The inventive concept of the present invention: the composite curing agent of the present invention includes mineral powder, lime, cement, early strength agent, thickener, and dispersant; the early strength agent includes calcium salt and silicate; the thickener includes polyvinyl amide and polyethylene glycol. The present invention adopts calcium salt and silicate compound as early strength agent, polyvinyl amide and polyethylene glycol compound as thickener, and combines mineral powder, lime, cement and dispersant. The components work together to improve the defects of titanium gypsum liquid height limit, difficult grading, low mechanical strength, etc., improve the strength and California bearing ratio (CBR) of titanium gypsum solidified soil, help to realize large-scale resource utilization of titanium gypsum, and reduce the content of soluble salts in titanium gypsum, thereby reducing the pollution of titanium gypsum solidified soil to the environment.
[0008] The reaction equation involved is as follows:
[0009] 3CaO·SiO2+nH2O=xCaO·SiO2·yH2O+(3-x)Ca(OH)2;
[0010] 2CaO·SiO2+mH2O=xCaO·SiO2·yH2O+(2-x)Ca(OH)2;
[0011] 4CaO·Al2O3·13H2O+3(CaSO4·2H2O)+14H2O=3CaO·Al2O3·3CaSO4·32H2O+Ca(OH)2;
[0012] 3CaO·Al2O3·3CaSO4·32H2O+2(CaO·Al2O3·13H2O)=3(3CaO·Al2O3·CaSO4·12H2O)+
[0013] 2Ca(OH)2+20H2O;
[0014] 4CaO·Al2O3·Fe2O3+2Ca(OH)2+6(CaSO4·2H2O)+50H2O=2[4CaO·(Al2O3·Fe2O3)·3CaSO4·32H2O];
[0015] 2[4CaO·(Al2O3·Fe2O3)·13H2O]+4CaO·(Al2O3·Fe2O3)·3CaSO4·32H2O=3[3CaO·(Al2O3·Fe2O3)·CaSO4·12H2O]+2Ca(OH)2+20H2O.
[0016] Therefore, a first aspect of the present invention provides a composite curing agent.
[0017] Specifically, the composite curing agent includes mineral powder, lime, cement, early strength agent, thickener, and dispersant;
[0018] The early strength agent includes calcium salt and silicate;
[0019] The thickeners include polyvinyl amide and polyethylene glycol.
[0020] Preferably, in terms of mass percentage, the composite curing agent includes 45-80% of mineral powder, 18-50% of cement, 0.9-11% of lime, 0.9-11% of early strength agent, 0.1-1.1% of thickener, and 0.1-1.1% of dispersant.
[0021] Further preferably, the composite curing agent comprises, by mass percentage, 50-77.8% of mineral powder, 20-45% of cement, 1-10% of lime, 1-10% of early strength agent, 0.1-1% of thickener, and 0.1-1% of dispersant.
[0022] Specifically, the mineral powder is provided by Guangdong Shaoguan Iron and Steel Jiayang New Materials Co., Ltd. and is made from Shaoguan Iron and Steel blast furnace slag after grinding. Its main chemical components are silicon dioxide, aluminum oxide, calcium oxide, and iron oxide. Since the mineral powder produced by Shaoguan Iron and Steel has a high content of silicon oxide and aluminum oxide, it can make up for the shortcomings of low silicon and aluminum content in titanium gypsum, optimize the ion ratio, form more calcium sulfonate, and effectively improve the early and late strength of titanium gypsum solidified soil.
[0023] Preferably, the cement comprises at least one of Portland cement, limestone cement and pozzolanic cement.
[0024] Specifically, the main components of the cement are C3S, 2CaO·SiO2 (C2S), 3CaO·Al2O3 (C3A), and 4CaO·Al2O3·Fe2O3 (C4AF), which are hydraulically hardened. The formed gel works together with calcium sulfonate to increase the strength of titanium gypsum solidified soil. Lime can dissolve the glass in the mineral powder and the mixture to stimulate the activity of the material. The addition of lime will also increase the supersaturation of Ca(OH)2, and Ca(OH)2 crystals will precipitate in advance, thereby shortening the induction period. The C3A in the solution is rapidly hydrated, and in the presence of calcium sulfate, calcium sulfonate is formed, which drives the consumption of iron and aluminum ions, and the number of crystals gradually increases, and then it is converted into monosulfide hydrated calcium aluminum sulfate (ferrite). As the hydration products increase, the hydration products fill the space originally occupied by water to form a material with a certain strength.
[0025] Preferably, in the early strength agent, the mass ratio of the calcium salt to the silicate is (3-5):1; further preferably, in the early strength agent, the mass ratio of the calcium salt to the silicate is (3.5-4.5):1; further preferably, in the early strength agent, the mass ratio of the calcium salt to the silicate is 4:1.
[0026] Preferably, in the thickener, the mass ratio of the polyvinyl amide and the polyethylene glycol is (8-10):1; further preferably, in the thickener, the mass ratio of the polyvinyl amide and the polyethylene glycol is (8.5-9.5):1; further preferably, in the thickener, the mass ratio of the polyvinyl amide and the polyethylene glycol is 9:1.
[0027] Specifically, calcium salts, as early strength agents, can improve early strength and form calcium sulfate with sodium sulfate, a soluble salt with a high content in titanium gypsum, reducing the content of sulfate. Silicates can promote the dissolution of cement minerals, accelerate the formation of hydration products, improve the slurry structure, and improve the frost resistance and impermeability of the slurry. The compounding effect of calcium salts and silicates can improve the strength of titanium gypsum-solidified soil and reduce the soluble salt content of titanium gypsum-solidified soil.
[0028] Specifically, polyvinyl amide is a polymer formed by polymerization of vinyl amide monomers, and its molecular formula is (C2H5NO) n , is a linear water-soluble high molecular polymer. As a thickener and modifier, it can well absorb soluble salt ions, increase the consistency of the slurry, and improve the strength of titanium gypsum stabilized soil. Polyethylene glycol can not only increase the consistency of the slurry, but also improve the fluidity of the slurry, making the polyacrylamide and the slurry mixed more evenly. The combined effect of polyacrylamide and polyethylene glycol can not only improve the strength of titanium gypsum stabilized soil, but also reduce the content of soluble salt ions in titanium gypsum stabilized soil.
[0029] Preferably, the dispersant comprises sodium hexametaphosphate.
[0030] Specifically, the sodium hexametaphosphate can improve the fluidity of the slurry and the dispersion of particles in the slurry, make the hydration more uniform, and form more uniform and complete crystals, further improving the strength; the complete crystal encapsulation will also reduce the dissolution of soluble salts, thereby reducing the soluble salt content.
[0031] Preferably, the calcium salt includes at least one of calcium chloride and calcium nitrate.
[0032] Preferably, the silicate includes at least one of sodium silicate and potassium silicate.
[0033] The second aspect of the present invention provides a method for preparing the composite curing agent according to the first aspect of the present invention.
[0034] Specifically, the preparation method of the composite curing agent comprises the following steps:
[0035] The various components are taken to form the composite curing agent.
[0036] A third aspect of the present invention provides titanium gypsum-solidified soil.
[0037] Specifically, the raw materials for preparing the titanium gypsum-solidified soil include titanium gypsum, the composite curing agent described in the first aspect of the present invention, and water.
[0038] Preferably, the mass of the composite curing agent is 3.0-4.0% of the sum of the mass of the titanium gypsum, the composite curing agent and water; further preferably, the mass of the composite curing agent is 3.2-3.8% of the sum of the mass of the titanium gypsum, the composite curing agent and water; even further preferably, the mass of the composite curing agent is 3.5% of the sum of the mass of the titanium gypsum, the composite curing agent and water.
[0039] The fourth aspect of the present invention provides a method for preparing the titanium gypsum solidified soil described in the third aspect of the present invention.
[0040] Specifically, the method for preparing the titanium gypsum solidified soil comprises the following steps:
[0041] (1) mixing the mineral powder, cement and lime to obtain powder A; mixing the early strength agent, thickener, dispersant and water to obtain solution B;
[0042] (2) Mixing the titanium gypsum with the powder A and solution B obtained in step (1) to obtain the titanium gypsum-solidified soil.
[0043] Preferably, when preparing solution B, the amount of water used is 0.4-0.6% of the total mass of the titanium gypsum, the composite curing agent and water; further preferably, when preparing solution B, the amount of water used is 0.45-0.55% of the total mass of the titanium gypsum, the composite curing agent and water; further preferably, when preparing solution B, the amount of water used is 0.5% of the total mass of the titanium gypsum, the composite curing agent and water.
[0044] Preferably, in step (2), the titanium gypsum is first mixed with the powder A and then mixed with the solution B to obtain the titanium gypsum-solidified soil.
[0045] The fifth aspect of the present invention provides an application of the composite curing agent described in the first aspect of the present invention or the titanium gypsum solidified soil described in the third aspect of the present invention in the resource utilization of titanium gypsum.
[0046] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0047] (1) The present invention adopts a compound of calcium salt and silicate as an early strength agent, a compound of polyvinyl amide and polyethylene glycol as a thickener, and combines mineral powder, lime, cement and dispersant. The components work together to improve the defects of titanium gypsum liquid height limit, difficult grading, low mechanical strength, etc., so that the titanium gypsum solidified soil has good mechanical properties, which is helpful to realize the large-scale resource utilization of titanium gypsum, and reduces the content of soluble salts in titanium gypsum, thereby reducing the pollution of titanium gypsum solidified soil to the environment.
[0048] (2) The method of preparing titanium gypsum solidified soil by treating titanium gypsum with a composite curing agent is simple, convenient for large-scale application, and has good economic, environmental and social effects, and has promotion value. DETAILED DESCRIPTION
[0049] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0050] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0051] Source information of relevant raw material components in the embodiments and application examples of the present invention:
[0052] The mineral powder comes from Guangdong Shaoguan Iron and Steel Jiayang New Materials Co., Ltd. It is made by grinding the slag from Shaoguan Iron and Steel's blast furnace. Its main chemical components are silicon dioxide, aluminum oxide, calcium oxide, and iron oxide.
[0053] The lime comes from Shaoguan Iron and Steel's roasting kiln, with a purity of 89%, and the impurities are mainly calcium carbonate.
[0054] Titanium gypsum comes from Jinan Yuxing Chemical Co., Ltd. The main components of titanium gypsum are iron, titanium, silicon, aluminum, calcium and a small amount of other geological elements.
[0055] Example 1
[0056] A composite curing agent comprises, by mass percentage, 70% of mineral powder, 21% of silicate cement, 5% of lime, 3% of early strength agent (the mass ratio of calcium chloride to sodium silicate is 4:1), 0.1% of thickener (the mass ratio of polyvinyl amide to polyethylene glycol 400 is 9:1), and 0.9% of dispersant sodium hexametaphosphate.
[0057] A method for preparing a composite curing agent comprises the following steps:
[0058] The composite curing agent is composed of mineral powder, lime, silicate cement, early strength agent, thickener and dispersant.
[0059] Example 2
[0060] A composite curing agent comprises, by mass percentage, 60% of mineral powder, 31% of silicate cement, 5% of lime, 3% of early strength agent (the mass ratio of calcium chloride to sodium silicate is 4:1), 0.1% of thickener (the mass ratio of polyvinyl amide to polyethylene glycol 400 is 9:1), and 0.9% of dispersant sodium hexametaphosphate.
[0061] A method for preparing a composite curing agent comprises the following steps:
[0062] The composite curing agent is composed of mineral powder, lime, silicate cement, early strength agent, thickener and dispersant.
[0063] Example 3
[0064] A composite curing agent comprises, by mass percentage, 70% of mineral powder, 21% of silicate cement, 7% of lime, 1% of early strength agent (the mass ratio of calcium chloride to sodium silicate is 4:1), 0.1% of thickener (the mass ratio of polyvinyl amide to polyethylene glycol 400 is 9:1), and 0.9% of dispersant sodium hexametaphosphate.
[0065] A method for preparing a composite curing agent comprises the following steps:
[0066] The composite curing agent is composed of mineral powder, lime, silicate cement, early strength agent, thickener and dispersant.
[0067] Application Example 1
[0068] A titanium gypsum solidified soil, whose preparation raw materials include titanium gypsum, the composite curing agent of Example 1 and water, the amount of the composite curing agent is 3.5% of the total mass of all the preparation raw materials of the titanium gypsum solidified soil, the amount of water is 0.5% of the total mass of all the preparation raw materials of the titanium gypsum solidified soil, and the balance is titanium gypsum.
[0069] A method for preparing titanium gypsum solidified soil comprises the following steps:
[0070] (1) mineral powder, silicate cement and lime are mixed uniformly to obtain powder A; polyvinyl amide, polyethylene glycol 400, sodium hexametaphosphate, calcium chloride and sodium silicate are dissolved in water to obtain solution B;
[0071] (2) Titanium gypsum was first mixed with powder A for 2 minutes, and then solution B was added and mixed for 3 minutes to obtain titanium gypsum solidified soil.
[0072] Application Example 2
[0073] A titanium gypsum solidified soil, the raw materials for its preparation include titanium gypsum, the composite curing agent of Example 2 and water, the amount of the composite curing agent is 3.5% of the total mass of all the raw materials for the titanium gypsum solidified soil, the amount of water is 0.5% of the total mass of all the raw materials for the titanium gypsum solidified soil, and the balance is titanium gypsum.
[0074] A method for preparing titanium gypsum solidified soil comprises the following steps:
[0075] (1) mineral powder, silicate cement and lime are mixed uniformly to obtain powder A; polyvinyl amide, polyethylene glycol 400, sodium hexametaphosphate, calcium chloride and sodium silicate are dissolved in water to obtain solution B;
[0076] (2) Titanium gypsum was first mixed with powder A for 2 minutes, and then solution B was added and mixed for 3 minutes to obtain titanium gypsum solidified soil.
[0077] Application Example 3
[0078] A titanium gypsum solidified soil, whose preparation raw materials include titanium gypsum, the composite curing agent of Example 3 and water, the amount of the composite curing agent is 3.5% of the total mass of all the preparation raw materials of the titanium gypsum solidified soil, the amount of water is 0.5% of the total mass of all the preparation raw materials of the titanium gypsum solidified soil, and the balance is titanium gypsum.
[0079] A method for preparing titanium gypsum solidified soil comprises the following steps:
[0080] (1) mineral powder, silicate cement and lime are mixed uniformly to obtain powder A; polyvinyl amide, polyethylene glycol 400, sodium hexametaphosphate, calcium chloride and sodium silicate are dissolved in water to obtain solution B;
[0081] (2) Titanium gypsum was first mixed with powder A for 2 minutes, and then solution B was added and mixed for 3 minutes to obtain titanium gypsum solidified soil.
[0082] Comparative Example 1
[0083] The difference between Comparative Example 1 and Example 1 is that the early strength agent in Comparative Example 1 is all calcium chloride and does not contain sodium silicate, and the rest is the same as Example 1.
[0084] Comparative Example 2
[0085] The difference between Comparative Example 2 and Example 1 is that the early strength agent in Comparative Example 2 is all sodium silicate and does not contain calcium chloride. The rest is the same as Example 1.
[0086] Comparative Example 3
[0087] The only difference between Comparative Example 3 and Example 1 is that the thickener in Comparative Example 3 is all polyethylene glycol 400 and does not contain polyvinyl amide. The rest is the same as Example 1.
[0088] Comparative Example 4
[0089] The only difference between Comparative Example 4 and Example 1 is that the thickener in Comparative Example 4 is all polyvinyl ammine, and does not contain polyethylene glycol 400. The rest is the same as Example 1.
[0090] Comparative Example 5
[0091] The difference between Comparative Example 5 and Example 1 is that no dispersant sodium hexametaphosphate is added in Comparative Example 5, and the rest is the same as Example 1.
[0092] Comparative Example 6
[0093] The difference between Comparative Example 6 and Example 1 is that the amount of mineral powder used in Comparative Example 6 is 21%, and the amount of silicate cement used is 70%, and the rest is the same as Example 1.
[0094] Comparative Example 7
[0095] The difference between Comparative Example 7 and Example 1 is that Comparative Example 7 uses an equal amount of early strength agent to replace lime, and the rest is the same as Example 1.
[0096] Comparative application example 1
[0097] The difference between Comparative Application Example 1 and Application Example 1 is that Comparative Application Example 1 uses the composite curing agent of Comparative Example 1, and the rest is the same as Application Example 1.
[0098] Comparative Application Example 2
[0099] The difference between Comparative Application Example 2 and Application Example 1 is that Comparative Application Example 2 uses the composite curing agent of Comparative Example 2, and the rest is the same as Application Example 1.
[0100] Comparative Application Example 3
[0101] The difference between Comparative Application Example 3 and Application Example 1 is that Comparative Application Example 3 uses the composite curing agent of Comparative Example 3, and the rest is the same as Application Example 1.
[0102] Comparative Application Example 4
[0103] The difference between Comparative Application Example 4 and Application Example 1 is that Comparative Application Example 4 uses the composite curing agent of Comparative Example 4, and the rest is the same as Application Example 1.
[0104] Comparative Application Example 5
[0105] The difference between Comparative Application Example 5 and Application Example 1 is that Comparative Application Example 5 uses the composite curing agent of Comparative Example 5, and the rest is the same as Application Example 1.
[0106] Comparative Application Example 6
[0107] The difference between Comparative Application Example 6 and Application Example 1 is that Comparative Application Example 6 uses the composite curing agent of Comparative Example 6, and the rest is the same as Application Example 1.
[0108] Comparative Application Example 7
[0109] The difference between Comparative Application Example 7 and Application Example 1 is that Comparative Application Example 7 uses the composite curing agent of Comparative Example 7, and the rest is the same as Application Example 1.
[0110] Performance Testing
[0111] The performance tests were carried out on the titanium gypsum solidified soil prepared in the corresponding application examples 1-3 and the comparative application examples 1-7. The specific test method includes the following steps:
[0112] (1) Weigh a certain amount of titanium gypsum solidified soil prepared in Application Examples 1-3 and Comparative Application Examples 1-7, pour it into the compaction cylinder in 3 layers and level the soil surface. The size of the compaction cylinder is φ152mm*116mm, and compaction is carried out in layers. The number of compactions is 98 times each time. The height of each layer of the sample after compaction should be roughly equal, and the soil surface at the junction of the two layers should be roughened; after compaction, the height of the sample exceeding the top of the compaction cylinder should be less than 6mm; use a soil trimming knife to dig along the inner wall of the casing, twist and remove the casing, measure the superheight, and take the average of multiple measured values with an accuracy of 0.1mm; carefully level the sample along the top of the compaction cylinder and remove the bottom plate; when the bottom surface of the sample exceeds the outside of the cylinder, it should be leveled; wipe the outer wall of the cylinder, weigh it, and measure it with an accuracy of 1g. The dry density (g / cm 3 ) = weighed mass / volume of compacted cylinder;
[0113] (2) Use a bulldozer to push the sample out of the compaction cylinder, and take two soil samples from the center of the sample, generally about 50g to 100g. Determine the moisture content of the soil in parallel, weighing accurately to 0.01g. The maximum allowable difference in the moisture content of the two soil samples should be ±1%;
[0114] (3) The optimum moisture content and maximum dry density of the titanium gypsum solidified soil are obtained through steps (1) and (2). According to the particle size of the titanium gypsum solidified soil, an unconfined test mold of φ100mm*100mm is selected as an unconfined compressive strength mold. According to the corresponding compaction requirements in the engineering test, the titanium gypsum solidified soil sample of corresponding mass is weighed, and the titanium gypsum solidified soil sample of corresponding mass is loaded into the unconfined test mold three times until all the corresponding mass of the titanium gypsum solidified soil is loaded into the mold. The mold is placed in a press with a displacement function for compression until the upper and lower pressure heads are pressed into the test mold and the pressure is maintained for 2 minutes before stopping the compression. The test piece is removed from the press and the test piece can be demolded immediately. The titanium gypsum solidified soil test piece is demolded with an electric demolding machine, and the mass and height are recorded and measured;
[0115] (4) The demoulded test piece was placed in a plastic bag for sealing and placed in a standard curing room for curing for 7 days (7d);
[0116] (5) Take out the cured test blocks and measure the unconfined compressive strength and soluble salt content.
[0117] The unconfined compressive strength and soluble salt content are tested in accordance with JTG3430-2020.
[0118] The performance test results of the titanium gypsum solidified soil prepared in Application Examples 1-3 and Comparative Application Examples 1-7 are shown in Table 1.
[0119] Table 1: Performance test results of titanium gypsum solidified soil prepared in Application Examples 1-3 and Comparative Application Examples 1-7
[0120]
[0121] It can be seen from Table 1 that the titanium gypsum solidified soil prepared by the present invention has good compressive strength, can meet the needs of road engineering, and has a low soluble salt content, which can reduce pollution to the environment and is more environmentally friendly; in addition, the titanium gypsum solidified soil also has a suitable maximum dry density and molding moisture content.
[0122] Compared with Application Example 1, Application Example 2 requires mineral powder to supplement the amount of aluminum ions because the titanium gypsum itself contains lower levels of aluminum oxide and silicon oxide. Application Example 2 reduces the amount of mineral powder and increases the amount of cement. In this system, the aluminum ion content in the system will decrease, thereby reducing the amount of calcium sulfonate crystals, reducing the crystal structure, decreasing the strength, and increasing the amount of soluble salts dissolved.
[0123] In Application Example 3, the amount of lime is increased and the content of the early strength agent is reduced. Since the solubility of calcium chloride is greater than that of calcium hydroxide, the supersaturation is delayed, the early strength decreases, and the compressive strength is lower than that of Example 1.
[0124] In comparative application example 1, calcium chloride is not added, and the hydration rate is delayed, resulting in a significant decrease in early strength. In comparative application example 2, sodium silicate is not added, and the mineral dissolution slows down, the hydration rate slows down, resulting in a decrease in early strength. It can be seen that calcium chloride and sodium silicate in the early strength agent are indispensable. The lack of either one will reduce the strength of titanium gypsum solidified soil and increase the content of soluble salts in the solidified soil.
[0125] In comparative application example 3, no polyvinyl amide was added, resulting in a decrease in colloid, a decrease in solution viscosity, an increase in water content, a decrease in strength, and a significant increase in the content of soluble salts. In comparative application example 4, no polyethylene glycol 400 was added, and the dispersibility of polyvinyl amide in the slurry decreased, the solution viscosity decreased, the water content increased, the strength decreased, and the content of soluble salts increased. It can be seen that polyvinyl amide and polyethylene glycol 400 are indispensable, and the lack of either one will significantly increase the content of soluble salts in titanium gypsum-solidified soil and reduce the compressive strength of titanium gypsum-solidified soil.
[0126] In comparative application example 5, no sodium hexametaphosphate was added, resulting in poor dispersibility of the system and uneven crystal distribution, which reduced the overall strength of the titanium gypsum-solidified soil.
[0127] Comparative Application Example 6 significantly increased the amount of cement and reduced the amount of mineral powder, resulting in poor element grading, a significant decrease in the strength of titanium gypsum-solidified soil, and an increase in the content of soluble salts.
[0128] In comparative application example 7, no lime is added, resulting in a weakening of the alkali excitation performance, which in turn causes a decrease in the strength of the titanium gypsum-solidified soil and an increase in the soluble salt content.
[0129] In summary, the present invention adopts a compound of calcium salt and silicate as an early strength agent, a compound of polyvinyl amide and polyethylene glycol as a thickener, and combines mineral powder, lime, cement and dispersant. The components work together to improve the defects of titanium gypsum liquid height limit, difficult grading, low mechanical strength, etc., so that the titanium gypsum solidified soil has good mechanical properties, which is helpful to realize the large-scale resource utilization of titanium gypsum, and reduces the content of soluble salts in titanium gypsum, thereby reducing the pollution of titanium gypsum solidified soil to the environment.
[0130] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A composite curing agent, characterized in that: Including mineral powder, lime, cement, early strength agent, thickener, dispersant; The early strength agent includes calcium salt and silicate; The thickeners include polyvinyl amide and polyethylene glycol.
2. The composite curing agent according to claim 1, characterized in that Calculated by mass percentage, the composite curing agent includes 45-80% of mineral powder, 18-50% of cement, 0.9-11% of lime, 0.9-11% of early strength agent, 0.1-1.1% of thickener and 0.1-1.1% of dispersant.
3. The composite curing agent according to claim 1, characterized in that In the early strength agent, the mass ratio of the calcium salt to the silicate is (3-5):
1.
4. The composite curing agent according to claim 1, characterized in that In the thickener, the mass ratio of the polyvinyl amide to the polyethylene glycol is (8-10):
1.
5. The composite curing agent according to any one of claims 1 to 4, characterized in that: The dispersant includes sodium hexametaphosphate; and / or the calcium salt includes at least one of calcium chloride and calcium nitrate; and / or the silicate includes at least one of sodium silicate and potassium silicate.
6. The method for preparing the composite curing agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: The various components are taken to form the composite curing agent.
7. A titanium gypsum solidified soil, characterized in that: The raw materials for preparing the composite curing agent include titanium gypsum, the composite curing agent according to any one of claims 1 to 5 and water.
8. The titanium gypsum-solidified soil according to claim 7, characterized in that: The mass of the composite curing agent is 3.0-4.0% of the sum of the mass of the titanium gypsum, the composite curing agent and water.
9. The method for preparing titanium gypsum solidified soil according to any one of claims 7 to 8, characterized in that: The following steps are involved: (1) mixing the mineral powder, cement and lime to obtain powder A; mixing the early strength agent, thickener, dispersant and water to obtain solution B; (2) Mixing the titanium gypsum with the powder A and solution B obtained in step (1) to obtain the titanium gypsum-solidified soil.
10. Use of the composite curing agent according to any one of claims 1 to 5 or the titanium gypsum cured soil according to any one of claims 7 to 8 in the resource utilization of titanium gypsum.